Structure and Conformation of Photosynthetic Pigments and Related Compounds. 11. 5,10,15,20-Tetrabutylbacteriochlorin - SENGE, MATHIAS (International Union of Crystallography, 1998)
The structure of the title compound, C36H50N4, is the first example of a tetra-meso-substituted free-base bacteriochlorin (2,3,12,13-tetrahydroporphyrin). While general structural characteristics are similar to other hydroporphyrins, the present structure presents one of the few examples of a hydroporphyrin with a planar macrocycle conformation.
PUBLISHED
Keywords: Chemistry; C36H50N4